Analisis Kesiapan Implementasi Rekam Medis Elektronik di Klinik Pratama Simpang Lima Husada - Mutiarasari, Shinta; Chotimah, Siti Noor; Nurvita, Silvia; Mayadilanuari, Aerrosa Murenda; Sumantiawan, Dody Indra (Universitas Nasional Karangturi, 2024)
The Ministry of Health is committed to transforming the health system, including the transformation of health technology. One of these technological developments is Electronic Medical Records (EMR). The purpose of this study was to determine the readiness of EMR implementation at Simpang Lima Husada Primary Clinic. This study used the CAFP EHR Readiness Assessment instrument to assess the readiness of EMR implementation so as to improve service quality and workflow efficiency. This type of research is descriptive qualitative research. Informants were determined by purposive sampling technique on 14 respondents. The results of the Management Capacity readiness study obtained a score of 15, which is at level III, which means that management capacity is very ready. The readiness of Financial and Budgetary Capacity and Operational Capacity received a score of 12 at level II, indicating a fairly good cost analysis and sufficient staff and infrastructure capacity. Technology Capacity Readiness received a score of 28, which is at level II, indicating that information technology readiness is adequate. Organizational Capacity Readiness scored 28 at level II indicating a fairly good understanding of the value of EMR. Overall, Simpang Lima Husada Primary Clinic scored 95 out of a score range of 44-96 (level II) indicating it is quite ready to implement EMR based on the CAFP EHR Readiness Assessment.